Magnetic Materials - Maaz, Khan (IntechOpen, 2016)
This book reports on the recent progresses in theory, application, and characterization of magnetic materials. It covers a broad spectrum of topics on magnetic materials with different shapes and morphologies such as transition metals, cylindrical and 2D ferromagnetic nanowires, core-shell nanowires, monoatomic-layered nanostructures, and nanocrystals. This book addresses diverse groups of readers with general background in physics and material science and also covers topics for the specialists in the field of magnetism. It is believed that this book will be interesting for the readers and will provide a solid foundation about the topic for the students, scientists, and engineers working in the field of material science and condensed matter physics.